Approximation of the maximally flat filter by using Bézier curve with an exponential function - Purahong, B.; Kanjanasurat, I.; Sithiyopasakul, P.; Chutchavong, V.; Pintavirooj, C. (My University, 2020)
This paper presents a design of filter by using Bézier curve with an exponential function. This paper used the advantage of The Bézier curve which had ability for approximation and an exponential function which had the adaptable parameters of the polynomial. It can adjust the characteristic of frequency response for the best performance. The simulation results of various setting show the frequency response, step response. The comparison of response between the Bernstein filter and Butterworth filter in order two show that the rise time of Bernstein filter better than Butterworth filter and Bézier curve filter has not overshoot. Furthermore, the stability Nyquist criterion has been used to guarantee the stability of the transfer function.